Vegetation limits the impact of a warm climate on boreal wildfires. Issue 4 (21st May 2013) - Girardin, Martin P.; Ali, Adam A.; Carcaillet, Christopher; Blarquez, Olivier; Hély, Christelle; Terrier, Aurélie; Genries, Aurélie; Bergeron, Yves
Summary: Strategic introduction of less flammable broadleaf vegetation into landscapes was suggested as a management strategy for decreasing the risk of boreal wildfires projected under climatic change. However, the realization and strength of this offsetting effect in an actual environment remain to be demonstrated. Here we combined paleoecological data, global climate models and wildfire modelling to assess regional fire frequency (RegFF, i.e. the number of fires through time) in boreal forests as it relates to tree species composition and climate over millennial time‐scales. Lacustrine charcoals from northern landscapes of eastern boreal Canada indicate that RegFF during the mid‐Holocene (6000–3000 yr ago) was significantly higher than pre‐industrial RegFF (ad c . 1750). In southern landscapes, RegFF was not significantly higher than the pre‐industrial RegFF in spite of the declining drought severity. The modelling experiment indicates that the high fire risk brought about by a warmer and drier climate in the south during the mid‐Holocene was offset by a higher broadleaf component. Our data highlight an important function for broadleaf vegetation in determining boreal RegFF in a warmer climate. We estimate that its feedback may be large enough to offset the projected climate change impacts on drought conditions.